2008
DOI: 10.1532/hsf98.20081087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Valve Annuloplasty and Replacement for Ischemic Mitral Valve Incompetence

Abstract: Correcting chronic IMR with either repair or replacement produces a good mid-term survival rate (approximately 75%) for survivors in NYHA classes I and II. In our study, mortality rates for the MVP and MVR groups were similar, even though the repair group had a lower mean ejection fraction and a higher NYHA class before and after the operation. We therefore conclude that repair is superior to replacement in treating ischemic mitral insufficiency. A prospective randomized study is needed to better compare these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 17 publications
3
20
1
Order By: Relevance
“…Our operative mortality and post-operative morbidity compare favorably with STS-predicted rates and rates from recent studies comparing outcomes after MV repair and MVR(19, 20). Other recent studies suggest that survival in high-risk populations such as ours may be similar between MVR and MV repair (13, 15, 20). We believe that the preservation of both leaflet chordae is essential in maintaining the left ventricular geometry and function.…”
Section: Discussionsupporting
confidence: 66%
“…Our operative mortality and post-operative morbidity compare favorably with STS-predicted rates and rates from recent studies comparing outcomes after MV repair and MVR(19, 20). Other recent studies suggest that survival in high-risk populations such as ours may be similar between MVR and MV repair (13, 15, 20). We believe that the preservation of both leaflet chordae is essential in maintaining the left ventricular geometry and function.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, recent studies have reported that early mortality of MVR is reducing, and is becoming similar to MVP for patients with IMR and similar EF [21,22]. Our study shows that in a population of high risk patients it is possible to achieve an acceptable and similar early mortality between MVP and MVR group.…”
Section: Discussionsupporting
confidence: 65%
“…One article was excluded because 20% of the patients were hemodynamically unstable and the etiology of MR was ischemic in only 38% of the patients [28]. Nine articles were selected for the final analysis [29][30][31][32][33][34][35][36][37].…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, our report is the first metaanalysis focusing specifically on repair versus replacement in [30] 100 0 0 100 0 All or most of the posterior leaflet was preserved during the procedure, and the entire anterior leaflet was excised Milano et al [31] 72 28 NA NA NA Partial or total chordal sparing was frequent Ngaage et al [32] NA some Most 0 The posterior mitral valve leaflet and subvalvular apparatus were preserved, and in some cases both leaflets were preserved Silberman et al [33] 100 0 100 0 0 Al-Radi et al [ [30] 30 a 100 (EF 35%) Silberman et al [33] NA NA 100 (EF < 25%) 100 (EF < 25%) Al-Radi et al [34] NA NA 12 (EF < 25%) 8 (EF < 25%) Mantovani et al [35] 45 (14) 44 (14) 16 (EF < 30%) Reece et al [36] NA NA 19 (EF < 30%) 11 (EF < 30%) Hickey et al [37] 40 (11) 43 (12) NA NA a Median is reported. * p < 0.05 compared to repair.…”
Section: Discussionmentioning
confidence: 99%